1997
DOI: 10.1002/art.1780400414
|View full text |Cite
|
Sign up to set email alerts
|

Induction of alternative splicing of HLA‐B27 by bacterial invasion

Abstract: Objective. Alternative splicing of certain class I major histocompatibility complex pre-messenger RNA (pre-mRNA) is known to lead to generation of a cell-free soluble protein analog. This study was undertaken to examine whether this process occurs with HLA-B27, whether the process is modified by arthritis-causing bacteria, and whether the assembly of the soluble molecules follows the same pathway as the integral parent molecules.Methods. Alternative splicing of pre-mRNA was analyzed by reverse transcriptase-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Interestingly, S. enterica serovar Typhimurium and Y. enterocolitica also induce alternative splicing of the premRNA of HLA-B27 with removal of the fifth exon. Because this fifth exon encodes the transmembrane domain, cell-free soluble HLA-B27 is generated (75).…”
Section: Hostmentioning
confidence: 99%
“…Interestingly, S. enterica serovar Typhimurium and Y. enterocolitica also induce alternative splicing of the premRNA of HLA-B27 with removal of the fifth exon. Because this fifth exon encodes the transmembrane domain, cell-free soluble HLA-B27 is generated (75).…”
Section: Hostmentioning
confidence: 99%
“…It has also been suggested that misfolding of HLA-B27 heavy chains, perhaps exacerbated by infection or other environmental factors, might lead to endoplasmic reticulum stress responses and inflammation independent of antigen presentation (8,9). Other effects of HLA-B27 on modulating bacteria-host interactions have also been proposed (10,11). Supportive evidence for the arthritogenic peptide hypothesis comes from population studies showing differential association of some HLA-B27 subtypes with AS.…”
mentioning
confidence: 99%
“…Indeed, an alteration in the splicing of B27 mRNA leading to the production of soluble HLA-B27 has been detected after infection of cell lines with Yersinia and Salmonella spp. (9). …”
Section: Discussionmentioning
confidence: 99%